Does attending a Delphi consensus conference impact surgeon attitudes? Survey results from the Americas HepatoPancreatoBiliary Association consensus conference on small asymptomatic pancreatic neuroendocrine tumors. Issue 5 (May 2019) - ,; Warner, Suzanne; Warren, Robert; St Hill, Charles; Celinski, Scott; Ly, Quan; Howe, James; Libutti, Steven; Maker, Ajay V.; Tran, Thuy B.; Coburn, Natalie; Fong, Zhi V.; et al.
Abstract: Background: Management of asymptomatic small well-differentiated (panNET) <2 cm remains controversial. A consensus conference was held on this topic. The impact of attending the conference and participating in the audience response survey on surgeon's clinical approach to pancreatic neuroendocrine tumors was assessed. Methods: Audience members were surveyed using a smartphone real-time response system at the beginning and end of the conference. Results: The majority of 75 attendees underwent fellowship training, and 30% had >10 years experience as attending surgeons. Previously published consensus statements on the topic were considered insufficient to guide surgical practice by 82% of attendees, and over 96% desired additional data. After review of the data, consensus statements, and decision-making process, a significant number of participants changed their opinions regarding indications for tissue biopsy (p = 0.001), size thresholds for excision (p = 0.002), and regional lymph node dissection (p = 0.002) independent of whether a consensus was reached by the content-expert panel. Conclusions: This represented the first Delphi process consensus on the topic, and the survey confirmed the topic as well-chosen and timely. Attendees changed opinions on management of panNET regardless of whether formal consensus was reached. Therefore, statements of consensus combined with presentation of literature and live discussion served to impact attendees' approach to this disease.